PENGARUH KEPEMILIKAN KELUARGA, KEPEMILIKAN INSTITUSI DAN KEPEMILIKAN ASING TERHADAP KINERJA KEUANGAN PERUSAHAAN - Asido Ivan; Surya Raharja (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to investigate the effect of family ownership, institutional ownership and foreign ownership on company performance in manufacturing companies listed on the Indonesia Stock Exchange. The independent variables in this study are family ownership, institutional ownership and foreign ownership with company performance as the independent variable.The sample used in this study were 68 companies in manufacturing listed on the Indonesia Stock Exchange (IDX) in 2016 - 2018. The type of data used in this study is secondary data, in the form of corporate financial statements. The data is then analyzed using multiple linear regression analysis, classical assumption test and hypothesis testing.The results of this study indicate that institutional ownership has a significant positive effect on company performance, while family ownership and foreign ownership have no significant effect on company performance. Institutional ownership is considered to have an important role in minimizing agency conflicts that occur between shareholders and management.The existence of institutional investors is considered capable of optimizing the supervision of management performance by supervising every decision made by management as company manager.